2004
DOI: 10.1210/er.2003-0020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cues to Implantation

Abstract: Successful implantation is the result of reciprocal interactions between the implantation-competent blastocyst and receptive uterus. Although various cellular aspects and molecular pathways of this dialogue have been identified, a comprehensive understanding of the implantation process is still missing. The receptive state of the uterus, which lasts for a limited period, is defined as the time when the uterine environment is conducive to blastocyst acceptance and implantation. A better understanding of the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
871
1
27

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 970 publications
(916 citation statements)
references
References 402 publications
17
871
1
27
Order By: Relevance
“…In addition, the occurrence in uterus at blastocyst implanting time of a high number of protective molecules (Leukemia Inhibitory Factor, heme oxygenase HO-1, IL-10, TGF-, etc. ), tolerogenic CD4 + CD25 + Foxp3 + T Reg cells (Zenclussen et al, 2006), and mast cells (Dey et al, 2004), together with the recent finding in long-term allograft tolerance systems of a novel T Reg -IL-9-mast cell immunosuppressive relationship [T Reg (TGF-)  IL-9  mast cell  (TGF-)] (Lu et al, 2006;Zenclussen et al, 2006;), is of substantial help for the formation of an immunotolerant and antiapoptotic implantation site. The presence of SV-IV in the uterus at this location following insemination could also contribute to the definition of the immunotolerant characteristics of the site, although the evidence that the protein is present in this location at the implantation time is only circumstantial (SV-IV is present in rat ejaculated semen in free and sperm-bound form; an SV-IV immunorelated protein has been found in rat uterine lysates and in human seminal plasma) (Ostrowski et al, 1979;Paonessa et al, 1984;Abrescia et al, 1985;Metafora et al, 1987a;Metafora et al, 1987b and unpublished results from our lab; Manco et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the occurrence in uterus at blastocyst implanting time of a high number of protective molecules (Leukemia Inhibitory Factor, heme oxygenase HO-1, IL-10, TGF-, etc. ), tolerogenic CD4 + CD25 + Foxp3 + T Reg cells (Zenclussen et al, 2006), and mast cells (Dey et al, 2004), together with the recent finding in long-term allograft tolerance systems of a novel T Reg -IL-9-mast cell immunosuppressive relationship [T Reg (TGF-)  IL-9  mast cell  (TGF-)] (Lu et al, 2006;Zenclussen et al, 2006;), is of substantial help for the formation of an immunotolerant and antiapoptotic implantation site. The presence of SV-IV in the uterus at this location following insemination could also contribute to the definition of the immunotolerant characteristics of the site, although the evidence that the protein is present in this location at the implantation time is only circumstantial (SV-IV is present in rat ejaculated semen in free and sperm-bound form; an SV-IV immunorelated protein has been found in rat uterine lysates and in human seminal plasma) (Ostrowski et al, 1979;Paonessa et al, 1984;Abrescia et al, 1985;Metafora et al, 1987a;Metafora et al, 1987b and unpublished results from our lab; Manco et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, this phenomenon of continuous decline of fecundity with age has also been confirmed in women over 35 years old [10][11][12]. The success of reproduction in eutherian mammals requires the uterus, a unique organ in the viviparity compared to other organisms ensuring full development of the new life in the maternal body [13]. The endometrial environment of uteri is proved to be one of the critical aspects to determine the reproductive capacity [14] and uterine factor has been proved to be critical for the decline of fecundity in both rodents and humans [4,15].…”
mentioning
confidence: 96%
“…Meanwhile, the epithelial cells undergo differentiation, accompanied with a dynamic junction complex remodeling and membrane maturation, leading to a decrease of epithelial polarity approaching implantation and a cell-shape transition from columnar to cubical configuration, 9 thus gradually achieving the capacity for blastocyst attachment on day 4 evening. 10 Therefore, a timely regulated epithelial membrane maturation and precisely maintained epithelial integrity is critical for embryo implantation. In this respect, recent studies have demonstrated that several transcription factors and signaling molecules, such as Msx1, KLF5, Wnt5a, Stat3 and FGFR2 are essential regulators during uterine epithelial transformation into receptivity.…”
mentioning
confidence: 99%